A criança surda “falando” pela brincadeira: infância, corpo e ethos¹ surdo - Maria Carmen Euler Torres (Desidades, 2020)
The main objective of this article is to identify playing as the main activity for children between 3 and 6 years old and as a reinvention of a culture creating the possibility of manifesting a playful culture. To deaf children in the process of language acquisition and therefore still without working command of a language, we seek to question the notion of childhood as that of ”one who cannot speak”, since a deaf child is able to bring about new ways to communicate their wishes and questionings. Understanding deaf people as a linguistic minority, colonized by the hegemony of speech, we want to regard deaf children as a possibility of invention or inception of new ways of being in the world as from their ethos.